Treg cell abnormality and its potential treatments in patients with primary immune thrombocytopenia - Lili Ji; Yunfeng Cheng (Clinical and Translational Discovery, 2022)
Abstract Primary immune thrombocytopenia (ITP) is an autoimmune heterogeneous disorder. T regulatory cells (Treg), play an important role in the pathogenesis of the disease. Numerical and functional disorders of Treg cells were both demonstrated in ITP. Thymocyte output decrease and instability of Treg cells contributed to the lower count of the cells. Several immune deregulatory defects of Treg cells further led to the disease's onset. Restoring Treg cells might have a therapeutic effect on ITP. New options focusing on increasing the number, or enhancing the immunomodulating function of Treg cells was reviewed in this manuscript.